Identifikasi Senyawa Flavonoid pada Beberapa Jenis Tanaman dengan Kromatografi Lapis Tipis: Literature Review - Putri, Anisa Oktaviana; Hati, Mentari Cahaya; Ishanti, Nasywa Putri; Ilham, Hilda Srivaliana (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2024)
Flavonoids are one of the secondary metabolites contained in plants, and can be used as anti-microbial, wound infection medicine, anti-fungal, anti-viral, anti-cancer and anti-tumor. This research reviews the isolation and identification of flavonoid secondary metabolite compounds from various parts of plants using the thin layer chromatography (TLC) method with the retention factor (Rf) value parameter. Data from various previous research articles are presented in tables, showing variations in Rf values obtained from the use of different eluents. The results showed that the eluent used influenced the Rf value, with ethanol eluent tending to provide high Rf values (above 0.9), indicating higher validity in flavonoid identification. This implication is important for understanding and interpreting the results of flavonoid analysis in plant research.